A Mixed Element Method for the Desorption-Diffusion-Seepage Model of Gas Flow in Deformable Coalbed Methane Reservoirs. (28th September 2014) - Yang, Lei
Abstract : We present a desorption-diffusion-seepage model for the gas flow problem in deformable coalbed methane reservoirs. Effects of fracture systems deformation on permeability have been considered in the proposed model. A mixed finite element method is introduced to solve the gas flow model, in which the coalbed gas pressure and velocity can be approximated simultaneously. Numerical experiments using the lowest order Raviart-Thomas (RT 0 ) mixed element are carried out to describe the dynamic characteristics of gas pressure, velocity, and concentration. Error estimate results indicate that approximation solutions could achieve first-order convergence rates.